2014
DOI: 10.1136/neurintsurg-2014-011175
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial carotid artery stenting followed by intracranial stent-based thrombectomy for acute tandem occlusive disease

Abstract: In acute tandem ICA-MCA/distal ICA occlusions, extracranial stenting followed by intracranial stent-based thrombectomy appears feasible, effective, and safe. Further evaluation of this treatment strategy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 25 publications
5
106
1
Order By: Relevance
“…Most interesting, these series report relevant differences of the revascularization efficacy, with TICI Ն 2b results ranging from 63% to 79% of cases and the rate of favorable clinical outcome spanning a range of 29%-76%. [5][6][7][8][9][10]22 Moreover, the reported rates of sICH range from 0% to almost 22%, most probably due to low numbers of included patients in single-center designs (On-line Table). Regarding the clinical outcome, our results (36% favorable outcome) lay between the results of the above-mentioned studies (52% and 29% respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interesting, these series report relevant differences of the revascularization efficacy, with TICI Ն 2b results ranging from 63% to 79% of cases and the rate of favorable clinical outcome spanning a range of 29%-76%. [5][6][7][8][9][10]22 Moreover, the reported rates of sICH range from 0% to almost 22%, most probably due to low numbers of included patients in single-center designs (On-line Table). Regarding the clinical outcome, our results (36% favorable outcome) lay between the results of the above-mentioned studies (52% and 29% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of sICH varies considerably in the literature, ranging from 0% to 20%. [5][6][7][8][9][10] Unfortunately, the small number of patients included in these series limits the validity of these findings. The aim of this retrospective study was to determine the risk of sICH and the angiographic results and the clinical outcome after emergency ICA stent placement in combination with anterior circulation thrombectomy in a large multicentric cohort.…”
mentioning
confidence: 89%
“…Mechanical thrombectomy of tandem ICAϪMCA occlusions has been described by several authors, including a proximal-to-distal approach with carotid stent placement to re-establish antegrade flow and access to the intracranial circulation for thrombectomy. [9][10][11][12][13][14] Despite this being necessary in acutely occluded or severe atherosclerotic carotid stenoses, acute cervical dissections can usually be traversed with distal-access catheter technology to target distal ELVOs, first with either direct aspiration and/or stent-retriever thrombectomy for rapid cerebral reperfusion. In our experience, the use of proximal balloon-guide catheters was deferred in preference to lower profile and distal-access aspiration catheters with or without stent retrievers to prevent further injury to the cervical carotid wall during thrombectomy.…”
Section: 27mentioning
confidence: 99%
“…Several investigators have demonstrated the feasibility of emergency ICA stenting combined with intracranial thrombectomy for tandem ICA-MCA occlusions with acceptable rates of successful recanalization, complications, and clinical outcomes. [9][10][11][12][13][14] In two of the recent multicenter trials that demonstrated a benefit of endovascular thrombectomy for AIS, carotid artery stent placement was necessary in 8.6%-12.9% of patients. 6,7 Few studies have focused on the endovascular management of spontaneous cervical dissections with or without tandem intracranial ELVOs in the AIS setting, often limited to small sample sizes because most dissections can be managed medically postthrombectomy.…”
mentioning
confidence: 99%
“…Carotid tandem occlusions are defined as both extra-cranial occlusion or stenosis of the internal carotid artery (ICA) and downstream intracranial vessel occlusion, which comprises a subgroup of patients that usually present poor recanalization rates under IVT and poor clinical outcomes 6 . Despite of the lack of clinical data from randomized trials on the best management course of acute carotid tandem occlusions, a combined recanalization strategy by means of carotid artery stenting and mechanical thrombectomy has recently shown promising results 7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25 . We aimed to assess the clinical and radiological data of patients who underwent carotid artery stenting (CAS) and endovascular treatment of acute ischemic stroke due to carotid tandem occlusions.…”
mentioning
confidence: 99%